The Potential Use of SSA and ISSA in Construction Field. A Review - Tan, Yeong Yu; Doh, Shu Ing; Chin, Siew Choo (IJISET, 2016)
Disposal of the sewage sludge is one of the major issue that been encounter most of the parties because it related to the environmental restrictions. Due to the heavy metals found in the sewage sludge, it is not permitted to dispose it in the soil or used as the fertilizer. Thus, investigation to use sludge in the construction field has been conducted. Sewage sludge which contain pozzolanic properties is used to replace cement, has been used to produce bricks, aggregates, ceramic and glass. Current cement production depended highly on non-renewable materials and requires high energy for production of which causes negative impact to the environment. Thus, sewage sludge which is renewable and environmental friendly could be used as alternative materials in the construction industry.